Prevalence of Refractive Errors in the INK Area, Durban, South Africa. Issue 3 (March 2016) - Mashige, Khathutshelo Percy; Jaggernath, Jyotikumarie; Ramson, Prasidh; Martin, Carrin; Chinanayi, Farai S.; Naidoo, Kovin S.
ABSTRACT: Purpose: To determine the prevalence and types of refractive errors in persons aged 35 years and older in the Inanda, Ntuzuma, and KwaMashu (INK) area of Durban, KwaZulu-Natal Province, South Africa. Methods: Refractive error data were obtained by autorefraction (Retinomax K-Plus; Nikon, Tokyo, Japan), retinoscopy, and subjective refraction. Refractive error was defined using spherical equivalents as myopia (<−0.5D) and hyperopia (>+0.5D). Astigmatism was defined as cylinder equal to or greater than −0.5D in either eye. Results: Participants' ages ranged from 35 to 90 years, with a mean of 53.05 ± 11.4 years. Women comprised 75% of the subjects. The prevalence of refractive error was 57.3%, with myopia 11.4%, hyperopia 37.7%, and astigmatism 25.7%. Myopia and astigmatism were significantly more prevalent in men (p < 0.01), whereas hyperopia was more prevalent in women (p < 0.01). Hyperopia was significantly associated with education (p < 0.01), whereas myopia and astigmatism were not (p = 0.09 and p = 0.15, respectively). Conclusions: Approximately 57.3% of the population 35 years and older in the INK area of Durban were affected by refractive errors, with myopia, hyperopia, and astigmatism being significantly associated with sex. This study suggests that there is a need for interventions to alleviate refractive error in the INK area as well as in other communities affected by the lack of access to affordable services.